ANALISIS PORTOFOLIO OPTIMAL MODEL INDEKS TUNGGAL SAHAM INDEKS ENERGY PERIODE 2016 – 2021 - Hasyim Mulya Abdillah; Renea Shinta Aminda; Immas Nurhayati (Economicus, 2023)
Ilnvestment ils the actilvilty olf ilnvestilng capiltal iln the present wilth the ailm olf gettilng prolfilts iln the fultulre. A realilstilc ilnvestolr will ilnvest hils fulnds iln stolcks that have hilgh retulrns bult wilth lolw rilsk. Tol milnilmilze arilsk, an olptilmal polrtfolilol ils folrmed. The olptilmal polrtfolilol ils a colmbilnatiloln olf expected retulrn wilth milnilmal rilsk. The silngle ilndex moldel ulnderliles that the market prilce ilndex ils iln lilne wilth the prilce olf seculriltiles. Thils stuldy ailms tol determilne the retulrn and rilsk. As well as tol chololse the olptilmal polrtfolilol and the prolpolrtiloln olf fulnds iln the Energy Sectolr Ilndex stolcks oln the Ilndolnesila Stolck Exchange. The results sholwed that there were 5 stolcks ilnclulded iln the olptilmal polrtfolilol wilth the prolpolrtiloln olf fulnds folr each stolck, namely HRUlM by 2%, MEDC by 10%, IlNDY by 7%, DOlIlD by 80% and PTROl by 1%. Wilth an expected retulrn olf 3.4% and a rilsk olf 8.1%. Careful ilnvestolrs can dilversilfy polrtfolilols rather than ilnvestilng entilrely iln ilndilvildulal stolcks, tol milnilmilze rilsk.